Anmeldelser - Falcon Møller, Dorthe (Danish Yearbook of Musicology, 1995)
Review of: Ingebjørg Barth Magnus og Birgit Kjellström: Musikmotiv i svensk kyrkokonst. Uppland framm till 1625 / Musial Motifs in Swedish Church Art. The Region of Uppland up to 1625. Translated by Michael Stevens. Svenska RIdIM-kommittén, Stockholm I993.